Enhancing Islamic Teacher Education through CIPP-Based Curriculum Evaluation - M Arif Musthofa; Kuswanto Kuswanto; Arif Al Hazmi (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to critically analyze and validate the applicability of the CIPP (Context, Input, Process, Product) evaluation model within the framework of Islamic education. Specifically, it seeks to test, verify, and deepen theoretical understanding of the CIPP model by examining its relevance, strengths, and limitations when applied to a religiosity-based educational context. Methodology: Using a qualitative descriptive-evaluative design, data were collected through observations and semi-structured interviews with 15 participants the Director of KMI, 3 supervisors, 6 teachers, and 5 students selected via purposive sampling. Data were analyzed thematically based on the four CIPP components. Main Findings: The religiosity-based curriculum fundamentally contrasts with the liberal-humanistic paradigm, which places humans as the ultimate center and measure of all things while neglecting spiritual and divine values. From the perspective of Islamic education, such a humanistic-liberal model is inherently incompatible, as it disregards the transcendental relationship between humans and their Creator. Novelty/Originality of this study: This study presents a novel contribution by revealing that the conventional application of the CIPP evaluation model, though comprehensive in managerial and procedural aspects, remains insufficient to address the complex realities of educational practice particularly within the realm of Islamic education. The model’s limitation lies in its inability to capture the spiritual (ilahiyah) dimensions that are essential to a religiosity-based curriculum. To overcome this gap, the study proposes an integrative framework termed MHI, which stands for Management, Humanitarian, and Ilahiyah components.